Cross-cultural adaptation of the Caregiver Reaction Assessment for use in Brazil with informal caregivers of the elderly - Fernanda Rochelly do Nascimento Mota; Janaína Fonseca Victor; Maria Josefina da Silva; Maria Eliana Peixoto Bessa; Valdicleibe Lira de Amorim; Maria Lígia Silva Nunes Cavalcante; Andréa Carvalho Araújo Moreira; Talita Matias Barbosa (SciELO, 2015)
This study aimed to carry out the cross-cultural adaptation of the Caregiver Reaction Assessment CRA for use in Brazil with informal caregivers of dependent elderly METHOD A methodological study, of five steps: initial translation, synthesis of translations, retro-translation, evaluation by a judge committee and a pre-test, with 30 informal caregivers of older persons in Fortaleza, Brazil. Content validity was assessed by five experts in gerontology and geriatrics. The cross-cultural adaptation was rigorously conducted, allowing for inferring credibility. RESULTS The Brazilian version of the CRA had a simple and fast application (ten minutes), easily understood by the target audience. It is semantically, idiomatically, experimentally and conceptually equivalent to the original version, with valid content to assess the burden of informal caregivers for the elderly (Content Validity Index = 0.883). CONCLUSION It is necessary that other psychometric properties of validity and reliability are tested before using in care practice and research.